Menganalisis Industri UMKM dan E-Commerce Pada Teknologi - Nurul Hasannah; Achmad Kaisi Amarco; Muhammad Yasin (Jurnal of Management and Social Sciences, 2025)
The background of this reseacrh is that there is a significate in the use of the internet lately that UMKM (Usaha Mikro Kecil dan Menengah) must be aware of, the impact of whisch is urgency of digital marketing as a solution to marketing media anxiety in supporting the promotion of sales of goods. This stigma strengthens the marketing carried out by UMKM actorst to be advanced and important to implement. Among them is the emergence of the use of social chat, E-businnes, social media, E-commerce, and so forth. The purpose of this research is so identify the use of capcin and jus 89 UMKM after applying digital marketing. This research method uses qualitative methods with a case study approach. Data collection techniques obtained through documentation, interviews, and observation. Meanwhile, checking the validity of the data is based on triangulation of techniques and sources. This data analysis here is applying Milles and Huberman’s data analysis. As for the results of this study, data was obtained that the effect of digital marketing on the income of UMKM capcin and jus 89 in Kediri City was significate, which was known from the increase in sales and high consumer interest.